Bio-Conjugated Polycaprolactone Membranes: A Novel Wound Dressing - Cai, Elijah Zhengyang (2016)
Background: The combination of polycaprolactone and hyaluronic acid creates an ideal environment for wound healing. Hyaluronic acid maintains a moist wound environment and accelerates the in-growth of granulation tissue. Polycaprolactone has excellent mechanical strength, limits inflammation and is biocompatible. This study evaluates the safety and efficacy of bio-conjugated polycaprolactone membranes (BPM) as a wound dressing. Methods: 16 New Zealand white rabbits were sedated and local anaesthesia was administered. Two 3.0×3.0 cm full-thickness wounds were created on the dorsum of each rabbit, between the lowest rib and the pelvic bone. The wounds were dressed with either BPM (n=12) or Mepitel (n=12) (control), a polyamide-silicon wound dressing. These were evaluated macroscopically on the 7th, 14th, 21st, and 28th postoperative days for granulation, re-epithelialization, infection, and wound size, and histologically for epidermal and dermal regeneration. Results: Both groups showed a comparable extent of granulation and re-epithelialization. No signs of infection were observed. There was no significant difference (P>0.05) in wound size between the two groups. BPM (n=6): 8.33 cm2, 4.90 cm2, 3.12 cm2, 1.84 cm2; Mepitel (n=6): 10.29 cm2, 5.53 cm2, 3.63 cm2, 2.02 cm2; at the 7th, 14th, 21st, and 28th postoperative days. The extents of epidermal and dermal regeneration were comparable between the two groups. Conclusions: BPM is comparable to Mepitel as a safe and efficacious wound dressing.